The Role of Police Administration in Infusing Collective Safe Disposal Behavior: An Empirical Study on The Djiboutian Citizens - Aden, Kadir; Aden Dirir, Sadik (Universitas Muhammadiyah Tangerang, 2023)
While Djibouti City's total solid waste production (without including other regions and rural municipalities) was only approximately 3 million tons in 2018, whereas, it is anticipated to increase to about 10.2 million tons by 2025. Despite the fact that landfilling is the only official treatment for the city of Djibouti's rising waste output, residents' management of general waste is nevertheless negatively impacted by the absence of waste segregation, owing to improper disposal methods and the lack of proper disposal sites which in retrospect led to illegal waste disposal. Therefore, the present study investigates the role of police administration in promoting collective safe waste disposal behavior among citizens. To do so, we conducted a comprehensive two-month open questionnaire on various Djiboutian social media platforms, ultimately garnering responses from 290 participants. Subsequently, we applied structural equation modeling. The findings indicate that police effectiveness and performance significantly and positively influence citizens' willingness to cooperate, subsequently fostering safe disposal behaviors. Conversely, police procedural justice had no significant impact on cooperation however, a direct positive effect from police procedural justice to safe disposal behavior had been detected. These insights aim to aid Djiboutian authorities in steering citizens toward more sustainable waste management practices. Meskipun produksi total limbah padat kota Djibouti (tanpa termasuk wilayah lain dan desa-desa) hanya sekitar 3 juta ton pada tahun 2018, namun diperkirakan akan meningkat menjadi sekitar 10,2 juta ton pada tahun 2025. Meskipun landfilling adalah satu-satunya metode pengelolaan limbah resmi bagi kota Djibouti yang menghadapi peningkatan produksi limbah, namun pengelolaan limbah umum oleh penduduknya tetap terpengaruh secara negatif oleh beberapa faktor. Hal ini termasuk ketiadaan segregasi limbah, metode pembuangan yang tidak tepat, dan kurangnya tempat pembuangan yang sesuai, yang pada akhirnya mengakibatkan pembuangan ilegal limbah. Oleh karena itu, penelitian ini menginvestigasi peran administrasi polisi dalam mempromosikan perilaku pembuangan limbah yang aman secara kolektif di kalangan warga. Untuk melakukannya, kami melakukan survei terbuka selama dua bulan di berbagai platform media sosial Djibouti, akhirnya mengumpulkan tanggapan dari 290 partisipan. Selanjutnya, kami menerapkan pemodelan persamaan struktural. Temuan kami menunjukkan bahwa efektivitas dan kinerja polisi secara signifikan dan positif memengaruhi kemauan warga untuk berkooperasi, yang pada gilirannya mendorong perilaku pembuangan limbah yang aman. Sebaliknya, keadilan prosedural polisi tidak memiliki dampak signifikan pada kerja sama, namun efek positif langsung dari keadilan prosedural polisi ke perilaku pembuangan limbah yang aman telah terdeteksi.